Helical pile capacity to torque ratio: a functional perspective - Souissi, Moncef, author; Siller, Thomas, advisor; Charlie, Wayne, committee member; Perko, Howard A., committee member; Troxell, Wade, committee member (Colorado State University. Libraries, 2019)
The capacity to installation torque ratio, Kt, has been used in the design of helical piles and anchors for over half a century. Numerous researches have been conducted to accurately predict this capacity-torque correlation factor. However, almost of all these Kt factors published or released by the manufacturers are based on shaft geometry alone, Hoyt and Clemence (1989). Recent full-scale tests (axial compression and tension) in clay, sand and bedrock have shown that the traditional Kt used, based on shaft size only, can be improved upon. The capacity to torque ratio seems to depend on the shaft size, shaft geometry, helix configuration, load direction and soil type, Lutenegger (2015). Seven hundred ninety-nine (799) full scale load tests in compression and tension were conducted on helical piles of varying shaft sizes, shaft geometry, helix configurations and different soil type (sand clay, and bed rock). The objective of this research is to determine the effect of these variables on the capacity torque correlation factor, develop a new empirical relationship between pile capacity and installation torque, and determine its reliability in comparison to the published Kt values used in the pile industry.